TINJAUAN KUALITAS GENTENG BERGELASIR PRODUK UNIT UJI DI UNIVERSITAS NEGERI YOGYAKARTA BERDASARKAN HASIL UJI LABORATORIUM BAHAN BANGUNAN - inotek, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract This Unit UJI Program aims to: (1) add income for UNY and its academic members, (2) supply facilities for the lecturers and students to conduct research and community service activities, (3) prepare new jobs in the glazuur material industry sector, and (4) give opportunities and working experience (new work field) for the UNY students. The development of the glazuur material products applies certain chemical reaction principles affected by composition (chemical substance concentration), reaction temperature, chemical characteristic, and physical characteristic of the chemical substance. Variations of the concentration, temperature, and chemical substance in a chemical reaction will produce various glazuur colors. The product development method was conducted by an experimental research in the Building Material Laboratory and the Chemical Laboratory UNY. The marketing strategy runs by promotion through regional and national expo activities and direct selling to consumers. The product marketing runs through PT. UNY MULTI UTAMA, the ceramic tile industry ”PWS” Godean, and Timboel Keramik Kasongan. The business products of the UJI unit in UNY are categorized into three groups: (1) glazuur materials, (2) glazuur tiles, and (3) glazuur ceramics. Various glazuur colours being produced are green, blue, brown, black, grey, yellow, chromic red, lead chromic red, and oxcyde. The business product specifications having been produced are: (1) the glazuur materials have an added value in aesthetics because they have various bright colors and the burning temperature is lower compared to the existing marketed glazuur materials, (2) the glazuur tiles have more aesthetical appearance, not porous, smoother surface, and higher elastical strength and lower water absorption compared to non-glazuur materials, (3) glazuur ceramics have smaller surface pores compared to non-glazuur materials so it will not wet although they are exposed with water for 48 hours. The liquefied test in the buffer solution with pH4 shows that there are metals in liquefied glazuur materials, but the amount is still below the threshold, so it will not endanger the environment. Although the incubation period of DP2M has been over, the business prospect of the glazuur material UJI unit Inotek, Volume 13, Nomor 2, Agustus 2009 136 is predicted to succeed because of the raw material availability in relatively cheap cost but relatively high product selling values. Keywords: glazuur materials, ceramics, and tiles